Blending agile methodologies to support automotive SPICE compliance. Issue 1 (21st October 2021) - Noureldin, Menna; Ghalwash, Atef; Abd‐Ellatif, Laila; ElGazzar, Mohamed
Abstract: Currently, agile methodologies are widely used as a light‐weight development process model based on short development cycles, which can satisfy frequent change requests from customers and stakeholders, and reach an efficient product delivery. On the other hand, most suppliers in the automotive industry are currently facing a challenge to comply to automotive SPICE (ASPICE) standard, which is a domain‐specific model of ISO/IEC 15504. Moreover, original equipment manufacturers (OEMs) have increasingly requested ASPICE compliance from their suppliers to accurately assess their process quality capability. This paper analyzes to what extent the ASPICE process areas were covered by agile and aims to propose a model based on integrating agile methodologies, as well as customize some agile practices so that it can fit in the Automotive SPICE process model and support automotive suppliers to achieve the required ASPICE rating. MAN.03, which is the process area for project management, was selected from the process reference model (PRM). Then, each base practice (BP) was mapped to the suitable agile methodology. Moreover, MAN.03 consists of 10 BPs, and each BP rating was measured to be N, P, L, or F. For Level 1, we applied Kanban on BP.4 and Scrum on the remaining BPs. For Level 2, we applied Scrum on all generic practices. We presented our results after deploying Kanban, and a restructured version of Scrum, which makes it in compliance with the automotive industry. The approach taken in this study could be applied in other process areas in the PRM afterwards. Abstract :